Analysis of point based image registration errors with applications in single molecule microscopy - Cohen,EAK; Ober,RJ (IEEE Transactions on Signal Processing, 2013)
We present an asymptotic treatment of errors involvedin point-based image registration where control point (CP)localization is subject to heteroscedastic noise; a suitable modelfor image registration in fluorescence microscopy. Assuming anaffine transform, CPs are used to solve a multivariate regressionproblem. With measurement errors existing for both sets of CPsthis is an errors-in-variable problem and linear least squaresis inappropriate; the correct method being generalized leastsquares. To allow for point dependent errors the equivalence of ageneralized maximum likelihood and heteroscedastic generalizedleast squares model is achieved allowing previously publishedasymptotic results to be extended to image registration. For aparticularly useful model of heteroscedastic noise where covariancematrices are scalar multiples of a known matrix (includingthe case where covariance matrices are multiples of the identity)we provide closed form solutions to estimators and derive theirdistribution. We consider the target registration error (TRE) anddefine a new measure called the localization registration error(LRE) believed to be useful, especially in microscopy registrationexperiments. Assuming Gaussianity of the CP localization errors,it is shown that the asymptotic distribution for the TRE and LREare themselves Gaussian and the parameterized distributions arederived. Results are successfully applied to registration in singlemolecule microscopy to derive the key dependence of the TRE andLRE variance on the number of CPs and their associated photoncounts. Simulations show asymptotic results are robust for lowCP numbers and non-Gaussianity. The method presented here isshown to outperform GLS on real imaging data.